The Pilsen Revolt of 1953 kindred by currency - Šlouf, Jakub 1982- (Lexington Books, 2022)
Public Protests in Pilsen in the Years 1948-1949 -- Worker Strikes at the Škoda Works in 1949-1953 -- Pilsen Strikes and Protests on 1 June 1953
"The text in this book is a revised English translation of the author's dissertation...published in Czech [in 2016]."--Introduction
Includes bibliographical references and index
Keywords: 1948-1953; Arbeitskampf / (DE-627)091393159 / (DE-2867)11348-5; Wechselkurspolitik / (DE-627)091399785 / (DE-2867)10722-5; Rationierung / (DE-627)091385237 / (DE-2867)11034-0; Geldpolitik / (DE-627)09136230X / (DE-2867)10382-3; Tschechoslowakei / (DE-627)091395607 / (DE-2867)16828-1; Strikes and lockouts / Czech Republic / Plzeň / History / 20th century; Monetary policy / Czech Republic / Plzeň / History / 20th century; Rationing / Czech Republic / Plzeň / History / 20th century